Control de inventarios y su incidencia en la situación financiera del distrito de salud 12d01 Baba-Babahoyo-Montalvo periodo 2017-2018 - Ramírez Abril, Jorge Alexis (2020)
The research work indicated Inventory Control and its impact on the Financial Situation, our objective was the evaluation of the procedures applied by the Health District in the management and control of inventories, its relationship with the Financial Accounting part, through The different investigation methods were able to show that the warehouse fulfills a very important part in the District, among the activities that are receiving all kinds of goods or existence, to be later distributed to the processes or Operating Units through a written authorization; The problem observed within the warehouse is the complexity of managing inventories, since it is evident the non-compliance with accounting administrative tasks, the staff is loaded with activities that are daily dispatch of stocks (medicines, office supplies, cleaning, supplies vector control, hardware materials, technical aids, among others); leaving aside the reconciliation of balances with the financial part, the physical verification of inventories, updating balances in the inventory control systems, ESBYE (control of assets and inventories), SGI (control of assets and inventories), normal control that is carried out in a spreadsheet database, therefore the lack of reconciliation of balances with the Financial department affects the Institution with losses in amounts and monetary values at the end of each financial year because they are not reflecting balances of the inventories in the financial statements reasonably. Keywords: Control, Inventory, Warehouse, Financial